(untitled) (Iranian Journal of Kidney Diseases, 2018)
Cystinosis is a rare autosomal recessive disorder resulting from defective lysosomal transport of cystine due to mutations in the cystinosin lysosomal cystine transporter (CTNS) gene. The clinical phenotype of nephropathic cystinosis is characterized by renal tubular Fanconi syndrome and development of end-stage renal disease during the first decade. Although metabolic acidosis is the classically prominent finding of the disease, a few cases may present with hypokalemic metabolic alkalosis mimicking Bartter syndrome. Bartter-like presentation may lead to delay in diagnosis and initiation of specific treatment for cystinosis. We report a case of a 6-year-old girl initially presenting with the features of Bartter syndrome that was diagnosed 2 years later with nephropathic cystinosis and a novel CTNS mutation.